KEMAMPUAN BERPIKIR KREATIF SISWA PADA PEMBELAJARAN IPAS MELALUI PENGGUNAAN BUKU INTERAKTIF DI SEKOLAH DASAR - Selpiah, Sinti; Fitriyani, Yani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the creative thinking skills of fourth-grade students at Tirtawangunan Elementary School in learning Natural and Social Sciences (IPAS) through the use of interactive books. Creative thinking skills are one of the important competencies in facing the challenges of the 21st century, which include aspects of fluency, flexibility, originality, and elaboration. The research method used is descriptive qualitative with data collection techniques in the form of observation, interviews, and documentation. The subjects of this study were fourth-grade students who participated in learning using interactive books for several meetings. The results of the study indicate that the use of interactive books can improve students' creative thinking skills, indicated by increased student involvement in the learning process, the diversity of ideas generated, and students' ability to develop and elaborate ideas in an original manner. Thus, interactive books are proven to be an effective learning medium in fostering students' creative thinking skills in IPAS learning in elementary schools.